OBSERVATION OF VITREOUS FEATURES USING ENHANCED VITREOUS IMAGING OPTICAL COHERENCE TOMOGRAPHY IN HIGHLY MYOPIC RETINOSCHISIS. Issue 9 (September 2019) - Song, Minlu; Shen, Mengxi; Zhou, Yanping; Zheng, Kairong; Zhai, Yuanqi; Xiao, Meichun; Wang, Xiaohan; Wang, Fenghua; Sun, Xiaodong
Abstract : Purpose: To observe features of the posterior vitreous and vitreoretinal interface in highly myopic eyes with retinoschisis using enhanced vitreous imaging optical coherence tomography. Methods: Comprehensive ophthalmologic examination and enhanced vitreous imaging optical coherence tomography were performed in 77 eyes of 63 patients with highly myopic retinoschisis. Two different modes of spectral domain optical coherence tomography were employed to estimate retinoschisis and the posterior vitreous features in optical coherence tomography images, respectively. The types and distribution of vitreoretinal interface abnormalities were also analyzed. Results: Complete posterior vitreous detachment (PVD) was identified in 55 eyes (71.4%) with a Weiss ring. Residual cortex was found in 39 eyes (70.9%) with complete PVD. Vitreoretinal interface changes, including vitreoretinal adhesion and epiretinal membrane (ERM), most frequently appeared in the macular area (47.3%), followed by the inferior arched vessels region (34.5%). In partial PVD eyes, vitreoretinal traction, vitreoretinal adhesion, and epiretinal membrane tended to be observed in the inferior and superior arched vessels regions (54.5 and 40.9%, respectively). Among all types of vitreoretinal interface abnormalities, epiretinal membrane comprised the largest proportion (46.8%) despite the status of PVD. The presence of inner layers of retinoschisis connoted a relatively high possibility of vitreoretinal interface abnormalities occurring. Conclusion: Enhanced vitreous imaging optical coherence tomography reveals a high prevalence of vitreoretinal interface abnormalities in highly myopic eyes with retinoschisis. Vitreous cortex tends to remain on the macular area in eyes with complete PVD. Our findings may lead to better guidance for the surgical treatment of highly myopic retinoschisis. Abstract : Using enhanced vitreous imaging optical coherence tomography, this study reveals a high prevalence of vitreoretinal interface abnormalities in highly myopic eyes with retinoschisis. Further understanding of the vitreoretinal interface factors would lead to better guidance for the surgical treatment of highly myopic retinoschisis.